Stable oxygen and carbon isotope ratios of speleothem WA-21-6-A - Paul S Wilcox; Manfred Mudelsee; Christoph Spötl; R Lawrence Edwards (PANGAEA, 2022)
The dataset includes speleothem carbon isotopes and oxygen isotopes used to reconstruct climate in southeastern Alaska during the past ~3,500 years. Speleothem WA-21-6-A was collected in Walkabout Cave (55.776° N, 133.195° W; 350 m.a.s.l.) on June 21, 2022. The data collection was completed between September 2021-March 2022. Stable isotopes were measured on a ThermoFisher Delta V isotope ratio mass spectrometer.
In: Wilcox, PS et al. (2022): WA-21-6-A and WB-21-5-A speleothem geochemistry [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.949778